From Subject to Participant: Ethics and the Evolving Role of Community in Health Research - Bromley, Elizabeth; Mikesell, Lisa; Jones, Felica; Khodyakov, Dmitry (American journal of public health (1971), 2015)
Belmont Report principles focus on the well-being of the research subject, yet community-engaged investigators often eschew the role of subject for that of participant. We conducted semistructured interviews with 29 community and academic investigators working on 10 community-engaged studies. Interviews elicited perspectives on ethical priorities and ethical challenges. Interviewees drew on the Belmont Report to describe 4 key principles of ethical community-engaged research (embodying ethical action, respecting participants, generalizing beneficence, and negotiating justice). However, novel aspects of the participant role were the source of most ethical challenges. We theorize that the shift in ethical focus from subject to participant will pose new ethical dilemmas for community-engaged investigators and for other constituents interested in increasing community involvement in health research.